The Sensitivity of Labor-Supply Parameter Estimates to Unobserved Individual Effects: Fixed- and Random-Effects Estimates in a Nonlinear Model Using Panel Data - Jakubson, George (Journal of Labor Economics, 1988)
Life-cycle models of labor supply predict the presence of an unobserved individual effect in the labor-supply equation that is correlated with observed explanatory variables, leading to an omitted variables bias in the cross section. I examine the sensitivity of parameter estimates to the presence of these effects, using fixed- and random-effect Tobit models. The estimated effects of children are too large in the cross section. The estimated intertemporal substitution elasticity ranges from 1.1 to 1.7. The results are similar for fixed- and random-effects models and for models using different specifications of the dependent variable.